Student Governance in Differentiated Learning at State Junior High School 1 Bulawa - Podungge, Lutfianita; Arwildyanto, Arwildyanto; Marhawati, Besse (Darul Yasin Al Sys, 2026)
The implementation of differentiated learning still faces substantial challenges, particularly in adapting content, processes, and learning products to meet the needs of diverse learners. This study aims to describe student governance in differentiated learning at SMP Negeri 1 Bulawa by examining: (1) planning; (2) organization; (3) implementation; and (4) assessment. Employing a descriptive qualitative approach, the study was conducted at SMP Negeri 1 Bulawa with data collected through observation, interviews, and documentation analysis, and analyzed using an interaction model of data analysis. The findings show that: (1) student governance planning is oriented toward the application of student-centered learning principles; (2) student organization is carried out collaboratively and flexibly; (3) the implementation of differentiated learning proceeds through adjustments to students’ readiness, interests, and learning profiles; and (4) assessment practices are comprehensive, continuous, and reflective. Overall, the implementation of differentiated learning at SMP Negeri 1 Bulawa has been successful and reflects the school’s concrete efforts to realize inclusive, adaptive, and student-centered learning, thereby strengthening governance practices that support differentiated instruction.